A compact Gysel power divider with ultra‐wide rejection band and high fractional bandwidth. Issue 6 (30th March 2021) - Zonouri, Seyed Abed; Hayati, Mohsen
Abstract: In this paper, one kind of miniaturized Gysel power divider (GPD) with ninth harmonic suppression is proposed. In this structure to weaken unwanted harmonics, radial and new trapezoidal‐shaped resonators are placed instead of the quarter‐wavelength transmission lines of the conventional GPD. Moreover, these resonators create eight transmission zeros and occupy small circuit sizes. For designing the proposed GPD, appropriate electrical lengths of transmission lines are selected. This GPD has high −15 dB fractional bandwidth, 71%, good isolation, > 15 dB, and compact sizes, 0.07 λg ×0.22 λg . The operating frequency of the designed power divider is 2.1 GHz that can be used in many WCDMA applications.